EMERGING TRENDS OF FUNDING SOURCES SMES WITH BIBLIOMETRIC ANALYSIS - Sulaiman, Haryaman Justisia; Depayanti, Ligwina (MOTIVASI, 2024)
The difficulty for SMEs is access to capital, which has been persistently tough; nonetheless, a solution is attainable. The paper presents an extensive bibliometric analysis of research trends and thematic development in funding sources for micro, small, and medium enterprises (SMEs), specifically concentrating on the timeframe from 2013 to 2024. It underscores the growing interest in innovative financing mechanisms such as equity crowdfunding, fintech, and digital finance, which are becoming essential for MSME funding. Traditional funding sources like bank loans and venture capital continue to be pertinent. However, there needs to be a discernible transition towards technology-enabled financing. The research highlights SMEs' difficulties in obtaining financing due to rigorous banking criteria, particularly in Indonesia. It proposes new study avenues centered on emergent subjects such as crowdfunding and the interaction between fintech and regulation. The results underscore the necessity for enhanced finance access and support systems to support SME growth and competitiveness.